A self-tunable Dynamic Vibration Absorber for tremor suppression - Teixeira, C. J. (2013)
We present a novel approach to Parkinson's Disease's (PD) tremor suppression based on a self-tunable Dynamic Vibration Absorber (DVA). The self-tuned DVA was designed, mathematically modeled, simulated and experimentally validated. For the experimental validation a wood beam, coupled to a vibration exciter, was used as an oscillating body. The control law for self-tuning was implemented and its effectiveness was investigated through experiments. Two types of input data were used to test the system performance. The first one was sinusoidal oscillations, where the input frequency could be varied; and the second a PD's waveform collected by sensors in patients and reproduced by the vibration exciter. The final self-tunable DVA system was able to suppress oscillations in the order of 98% and, maximum, 60%, respectively. This self-tunable DVA presents some biomedical advances and novelties. It has the ability to change its resonant frequency and better adapt itself to the patients inconstant tremor. Also, in a self-tunable DVA based on its mass, the components are lighter and smaller allowing clinical appliance in PD patients.